Effect of doping on the structural properties of ZnO nanowires synthesised by ultrasonic-assisted immersion technique / Mohamad Dzulfiqar Bakri ... [et al.] - Bakri, Mohamad Dzulfiqar; Malek, Mohd Firdaus; Mohammad, Maryam; Mohamed, Ruziana; Hisam, Rosdiyana; Abdullah, Mohd Hanapiah; Fadzilah Suhaimi, Mohd Husairi; Tetsuo, Soga; Mahmood, Mohamad Rusop (Universiti Teknologi MARA Shah Alam, 2023)
Various procedures for producing high-quality zinc oxide (ZnO) nanowires (ZnO NWs) have been developed. Nevertheless, most of it rely on harsh circumstances such as high temperature, high pressure, costly materials, and complicated procedures. As a result, this study introduces an alternative ultrasonic-assisted immersion technique due to its many advantages such as low cost, ease of handling, and low energy consumption, as well as studying the effect of different precursors on the morphological, structural, and optical properties of the ZnO NWs, thus supporting and consolidating previous discoveries and providing a clearer understanding of the mechanism of ZnO formation. The most promising desirable features have been demonstrated for chromium doped ZnO NWs. Field emission scanning electron microscopy (FESEM) was used to examine the surface morphology of the samples, and x-ray diffraction (XRD) and UV-visible (UV-Vis) were utilised to investigate the structural and optical characteristics of the ZnO NWs. It was discovered that inserting Cr as a dopant for ZnO enhanced ZnO NWs by preventing quick electron-hole recombination, revealing it as the best dopant. This id due to reduced band gap (3.231 eV), relax strain (−0.2383%) and stress (0.560 GPa), and near zero porosities.